EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DAN TEAM ASSISTED INDIVIDUALIZED (TAI) PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) DITINJAU DARI ADVERSITY QUOTIENT (AQ) SISWA KELAS VIII SMP NEGERI SE-KABUPATEN KARANGANYAR - Pambudi, Pangesti Arum; Mardiyana, Mardiyana; Sari Saputro, Dewi Retno (Jurnal Pembelajaran Matematika, 2016)
Abstract: The aim of this research was to determine the effect of learning models on mathematics achievement viewed from studentsâ AQ. The learning models compared were Jigsaw cooperative learning, TAI cooperative learning, and direct learning. The type of this research was quasi-experimental research. Population was all of state Junior High School students in Karanganyar Regency on academic year 2015/2016. Samples for group experiment 1 (Jigsaw cooperative learning model) were 98 students, group experiment 2 (TAI cooperative learning model) were 99 students, and control class (direct learning model) were 98 students. The data were collected using documentary method, AQ questionnaire, and mathematics learning achievement test. Data analysis technique used two-ways analysis of variance with unbalanced cells. The conclusion of this research as follows: (1) The Jigsaw cooperative learning model makes better mathematics learning achievement than TAI cooperative learning model and direct learning model, while TAI cooperative learning model makes better mathematics learning achievement than direct learning, (2) Climber students get better mathematics learning achievement than students Camper students and Quitter students, while Camper students get better mathematics learning achievement than Quitter students, (3) for every learning model, Climber students get better mathematics learning achievement than Camper students and Quitter students, while Camper students get better mathematics learning achievement than Quitter students, (4) for every categories, Jigsaw cooperative learning model makes better mathematics learning achievement than TAI cooperative learning model and direct learning model, while TAI cooperative learning model makes better mathematics learning achievement than direct learning model.Key words : Jigsaw, Team Assisted Individualized, Adversity Quotient